Upregulated baseline plasma CCL19 and CCR7 cell-surface expression on monocytes in early rheumatoid arthritis normalized during treatment and CCL19 correlated with radiographic progression. (March 2014) - Ellingsen, T; Hansen, I; Thorsen, J; Møller, BK; Tarp, U; Lottenburger, T; Andersen, LS; Skjødt, H; Pedersen, JK; Lauridsen, UB; Svendsen, A; Lindegaard, H; et al.
<x xml:space="preserve">Abstract</x> Objectives: The aim of this study was to measure, in early rheumatoid arthritis (RA) patients, the concentration of CC-chemokine ligand 19 (CCL19) in plasma and the cell-surface expression of CC-chemokine receptor 7 (CCR7) on circulating monocytes and CD4+ T lymphocytes and to analyse correlations with disease activity and 5-year radiographic progression. Method: In disease-modifying anti-rheumatic drug (DMARD)-naïve RA patients (disease duration < 6 months), we measured plasma CCL19 by enzyme-linked immunosorbent assay (ELISA) (n = 160) and CCR7 cell-surface expression on monocytes and CD4+ T lymphocytes by flow cytometry (n = 40) at baseline and after 1 year of treatment with methotrexate (MTX) or methotrexate+cyclosporin A (MTX/CyA). Radiographic progression was scored by the van der Heijde-modified Total Sharp Score (TSS) from 0 to 5 years. Results: Increased baseline CCL19 (median 85 pg/mL, range 31–1008 pg/mL, p = 0.01) decreased after 1 year (median 31 pg/mL, range 31–1030 pg/mL, p < 0.001) and 5 years (median 31 pg/mL, range 31–247 pg/mL, p < 0.001) to a level below the controls (n = 45) (median 60 pg/mL, range 31–152 pg/mL). Baseline plasma CCL19 levels [p = 0.011, 95% confidence interval (CI) 0.0030–0.0176], anti-cyclic citrullinated peptide (anti-CCP) antibody status (p = 0.002, 95% CI 0.61–2.38), and TSS > 0 at baseline (p < 0.001, 95% CI 1.21–3.16) were independent predictors of 5-year radiographic progression evaluated by multiple logistic regression in contrast to never smoked, C-reactive protein (CRP), gender, age, number of tender (NTJ) and swollen joints (NSJ), and 28-joint Disease Activity Score (DAS28). Increased CCR7 expression on monocytes (p = 0.008) correlated to CRP (p = 0.006, r = 0.52) and normalized (n = 15) after 1 year (p = 0.02). Conclusions: In DMARD-naïve RA patients, CCL19 plasma level and CCR7 surface expression on monocytes were upregulated and normalized after 1 year of treatment. Increased baseline plasma CCL19 level, anti-CCP antibody status, and TSS > 0 at baseline correlated independently with 5-year radiographic progression.